Life Satisfaction Differences between Workers and Non-Workers - The Value of Participation per se - Bernard M.S. van Praag; Ada Ferrer-i-Carbonell (Tinbergen Institute, 2002)
Is working more than monetary income? This paper attempts to give an answer to this question on the basis of the German Socio-economic Panel data set. By comparing the satisfaction with life between workers and non-workers with the same household income, the monetary value of participating in the labour force is assessed. It is found that this monetary value is substantial for many individuals and that it varies strongly with personal characteristics such as age and gender.Women suffer less than men when loosing their job. Individuals about 65 and over do not seem to attach much value to working besides the income it generates.
Keywords: C23; C25; J20; 330; Employment; Satisfaction; Subjective labour costs; Unemployment; Erwerbstätigkeit; Arbeitslosigkeit; Lebensqualität; Deutschland